2018
DOI: 10.1002/1873-3468.13243
|View full text |Cite
|
Sign up to set email alerts
|

Interaction network of the mitochondrial outer membrane protein Mcp3

Abstract: Mitochondria are organelles containing two membranes that are distinct in composition and function. A role of the mitochondrial outer membrane (MOM) is to mediate contact of the organelle with the rest of the cell. In yeast, the MOM contains about 40 different integral proteins. Recently, we described the MOM protein Mcp3, which can serve as a multicopy suppressor of loss of ERMES complex that mediates mitochondria-endoplasmic reticulum contacts. To shed further light on the role of Mcp3 in the MOM, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Overexpression of none of these proteins resulted in a growth defect of psd1 Δ cells (Figure 5C). Additionally, we tested the overexpression of the third Mdm10-complementing protein, Mcp3, which was recently identified as an outer membrane component (Sinzel et al , 2016, 2018). Again, we did not observe an effect on the growth of cells lacking Psd1 (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of none of these proteins resulted in a growth defect of psd1 Δ cells (Figure 5C). Additionally, we tested the overexpression of the third Mdm10-complementing protein, Mcp3, which was recently identified as an outer membrane component (Sinzel et al , 2016, 2018). Again, we did not observe an effect on the growth of cells lacking Psd1 (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…Although other sites of contact for MOM and MIM have been proposed, such as the interaction of the translocase of the outer membrane (TOM) and translocase of the inner membrane (TIM) machineries (Waegemann et al , 2015), their relevance to mitochondrial lipid trafficking is unknown. Recently, we demonstrated that another MOM protein, Mcp3, which functions as a weak suppressor of loss of ERMES function, interacts physically with the MIM protein Aim19 (Sinzel et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In S. cerevisiae Fzo1 is an important mitochondrial integral protein involved specifically in the fusion of outer membranes which promotes mitochondrial fusion. Initiation of membrane fusion in other organelles requires small GTPases and SNAREs whereas in mitochondria dynamin-like large GTPases and the mitofusins (Mfn1 and Mfn2 in mammals; Fzo1 in yeast) are required [62,63,115,116]. Like Dnm1, Fis1 (fission 1) proteins have been shown to be essential for mitochondrial fission after forming a complex with each other to induce mitophagy and promote cell apoptosis [73,117].…”
Section: Mitochondrial Fission and Fusionmentioning
confidence: 99%